2021
DOI: 10.12740/pp/onlinefirst/112442
|View full text |Cite
|
Sign up to set email alerts
|

Transsexualism or psychotic disorder? A case study

Abstract: Celem artykułu jest analiza przypadku mężczyzny z diagnozą schizofrenii paranoidalnej, który doświadcza urojeń i omamów dotyczących zmiany płci, oraz krótki przegląd literatury. Dane zaprezentowane w studium przypadku zostały zebrane podczas wywiadu klinicznego, w ciągu półrocznego procesu diagnostycznego. Wywiad miał postać częściowo ustrukturalizowaną, wykorzystano również baterię testów - Minesocki Wielowymiarowy Inwentarz Osobowości 2 (MMPI-2), Ustrukturalizowany Wywiad Kliniczny do Badania Zaburzeń z Osi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…Delusions of sex change were reported for 26% of 127 people diagnosed with schizophrenia. 24,25 Although coenesthetic hallucinations involving sex change are not always easy to distinguish from transgenderism or gender dysphoria, 26,27 we have, on the basis of the descriptions given, decided to include these cases in our overview.…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%
“…Delusions of sex change were reported for 26% of 127 people diagnosed with schizophrenia. 24,25 Although coenesthetic hallucinations involving sex change are not always easy to distinguish from transgenderism or gender dysphoria, 26,27 we have, on the basis of the descriptions given, decided to include these cases in our overview.…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%
“…18 Another review indicated that up to 6% of patients with gender dysphoria had a comorbid psychotic disorder, and listed a number of case studies where antipsychotic treatment was associated with a reduction or resolution of gender dysphoria. 19 Despite this, the WPATH standards appear more concerned that comorbid psychosis might prevent gender diverse patients from accessing the GAMOC than that patients with psychosis might be harmed by the affirmation of psychotic beliefs. 1 Close reading of GAMOC guidelines reveals a fatal deficiency.…”
Section: The Circular Assumptions Of Gender-affirming Carementioning
confidence: 99%
“…Trečiuoju atveju lyties disforija ir šizofrenija gali būti traktuojami kaip neurologinės raidos sutrikimai. Ketvirtuoju atveju šizofrenija sergančio asmens lyties tapatumui turi įtakos kognityvinio, emocinio ir socialinio funkcionavimo trūkumai ikipsichotinėje stadijoje [7].…”
Section: Diskusijaunclassified
“…Pasaulio sveikatos organizacijos išleistos Tarptautinės ligų klasifikacijos vienuoliktojoje versijoje (TLK-11) terminas "transseksualizmas" pakeistas į "lyties nesuderinamumas paauglystėje ar pilnametystėje". Svarbus šioje klasifikacijoje atliktų pakeitimų aspektas yra transseksualumo demedikalizacija [7]. Nyderlanduose atliktas tyrimas patvirtino lyties disforijos ir šizofrenijos pasireiškimą kartu.…”
Section: Diskusijaunclassified